2020
DOI: 10.1371/journal.pone.0239201
|View full text |Cite
|
Sign up to set email alerts
|

Time after ostomy surgery and type of treatment are associated with quality of life changes in colorectal cancer patients with colostomy

Abstract: Purpose Quality of life in colorectal cancer patients may be affected by colostomy and treatment, but relevant studies are still scarce and contradictory. The present study aimed to evaluate the association between colostomy time and treatment type with quality of life in colorectal cancer patients. Methods A prospective observational study of 41 patients with colorectal cancer was conducted on three occasions T0, T1 and T2 (0–2; 3–5 and 6–8 months after ostomy surgery, respectively). The treatments prescrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
1
16
0
1
Order By: Relevance
“…Lastly, certain treatment‐related and socioeconomic factors can also affect psychosocial experience of young‐onset CRC patients. Consistent with previous studies on CRC treatment, 32 , 33 the need for additional treatment such as chemotherapy and stoma were also associated with poorer outcomes in young‐onset CRC patients. For young‐onset CRC patients, given that they are often diagnosed at a more advanced stage, 34 the intensity of their treatment plans will consequently be greater and may therefore contribute to greater psychosocial impact.…”
Section: Discussionsupporting
confidence: 88%
“…Lastly, certain treatment‐related and socioeconomic factors can also affect psychosocial experience of young‐onset CRC patients. Consistent with previous studies on CRC treatment, 32 , 33 the need for additional treatment such as chemotherapy and stoma were also associated with poorer outcomes in young‐onset CRC patients. For young‐onset CRC patients, given that they are often diagnosed at a more advanced stage, 34 the intensity of their treatment plans will consequently be greater and may therefore contribute to greater psychosocial impact.…”
Section: Discussionsupporting
confidence: 88%
“…It has been proven that a stoma may lead to the person quitting work, which can cause financial difficulties. Interestingly, among the results of our research, we could not find any studies which proved that there were financial difficulties in a group of patients with either permanent or temporary ostomies [ 27 , 84 ].…”
Section: Methodsmentioning
confidence: 60%
“…Males are more often negatively affected by the surgery. However, it has been proven that some surgical approaches have less of an impact on sexual functioning [ 20 , 28 , 37 , 38 , 44 , 68 , 84 , 96 , 97 , 98 , 99 ]. Taking female sexual functions into account, there is a report of them decreasing over time.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we should provide long-term intervention measures to improve CRC survivors' quality of life and fatigue. Silva et al [ 15 ] reported that colostomy enhances the patients’ quality of life for 3–5 mo and improves it 6–8 mo after the operation. By contrast, late-stage radiotherapy and chemotherapy can harm the quality of life.…”
Section: Discussionmentioning
confidence: 99%